Dynamics of stakeholder engagement in mega transport infrastructure projects. Issue 7 (22nd July 2019) - Erkul, Mehmet; Yitmen, Ibrahim; Celik, Tahir
Abstract : Purpose: The purpose of this paper is to investigate the practice of stakeholder engagement as a social network dynamics for stakeholder satisfaction and project success in the lifecycle of mega transport infrastructure projects (MTIPs). Design/methodology/approach: Hypotheses indicating the positive relationships between stakeholders' effective attributes, stakeholder engagement as social network dynamics and project success through stakeholders' satisfaction have been developed. Based on a questionnaire survey and semi-structured interviews, responses have been gathered from the representative groups and organizations on their social network dynamics for their satisfaction and project success. A hypothesized structural equation model has been tested using AMOS statistical software package. Findings: The analysis highlighted the engagement of the stakeholders within the strategic intents of the project with the public needs and expectations. The model depicts the processes of building social network models based on the capturing of the project's data in relation to the stakeholders' communication and satisfaction across the key issues for success in the lifecycle of MTIP. Practical implications: The model is applicable on most MTIP with a diverse stakeholder base and the underlying complexity associated with the community participation and consultation processes. The model will also support wider stakeholder engagement in the planning of MTIP with optimal operationalization and service delivery from a community perspective. Originality/value: The research involves an approach for rationalizing the stakeholder engagement policies of the MTIPs by providing an empirically grounded model simultaneously linking various aspects of stakeholder effective attributes, stakeholder engagement and their relationships to stakeholder satisfaction and project success in MTIPs.